Wpływ kompostowania na ograniczenie emisji metanu ze składowanych odpadów komunalnych = Impact of composting to the limitation of methane emissions from municipal waste landfills - Myszograj, Sylwia; Kozłowska, Katarzyna; Gramza, Piotr (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The legal acts relating to waste disposal indicate the possibility of achieving the objectives of reducing greenhouse gases, by the recognition of methane from landfills and exclusion of biodegradable waste from the stream directed to the storage.
Keywords: gazy cieplarniane; metan; odpady komunalne; kompostowanie; greenhouse gases; methane; municipal waste; composting